Gastrointestinal Parasite infections in Chacma Baboons (Papio ursinus) of the Cape Peninsula, South Africa: the influence of individual, group, and anthropogenic factors - Ravasi, Damiana Francesca Celine (Department of Biological Sciences, 2014)
Habitat disturbance can lead to the alteration of host-parasite dynamics and ultimately influence the mechanisms that regulate wildlife populations. This study investigates whether anthropogenic changes in the Cape Peninsula, South Africa, have affected gastrointestinal parasite infections in a free-living population of chacma baboons (Papio ursinus). Data on parasite diversity and prevalence were obtained from 616 faecal samples collected from over 350 individuals in eight troops (six from the Cape Peninsula, one from Pringle Bay, and one from Wildcliff Nature Reserve) between July 2006 and August 2007. Faeces were processed using a modified formalin-ether sedimentation technique and helminth eggs and protozoan cysts were identified. The helminth and protozoan fauna of the Cape Peninsula baboon population was similar to both neighbouring and geographically disparate chacma baboon populations in South Africa. Distribution of helminth infection within a troop was influenced by the age of the host but not by other individual-level traits (i.e., gender and female reproductive and social status). Protozoan and helminth species richness was highest in the troop (Kanonkop) with the least human contact and the most pristine indigenous vegetation and was lowest in the troop (Tokai) with the highest levels of anthropogenic disturbance. Prevalences of the nematodes Trichuris sp. and Oesophagostomum sp. were highest in the troop (Da Gama Park) with the most frequent human interactions. A series of potential host-intrinsic (e.g., host sex and age) and host-extrinsic (e.g., troop characteristics, climate) determinants of host-parasite dynamics were investigated but failed to explain the observed inter-troop variations in parasite infections. Molecular analyses of the ubiquitous and highly prevalent nematode, Trichuris sp., provided evidence of two genetically distinct Trichuris species, including a newly identified baboon parasite, named T. papionis, and another that strongly resembles (91% similarity between ITS1-5.8S rDNA-ITS2 sequences) the human T. trichiura. The latter finding provides the first evidence of a likely reverse zoonotic infection of baboons with human parasites and provides management authorities with a strong motivation to restrict the spatial overlap between the humans and baboons in the Cape Peninsula and indeed other regions of the Western Cape. Keywords: Papio ursinus - chacma baboon - parasites - urbanization - Trichuris - molecular